The Primary Cilium on Cells of Developing Skeletal Rudiments; Distribution, Characteristics and Response to Mechanical Stimulation - Shea, Claire A.; Murphy, Paula (Frontiers in Cell and Developmental Biology, 2021)
Embryo movement is important for tissue differentiation and the formation of functional skeletal elements during embryonic development: reduced mechanical stimulation results in fused joints and misshapen skeletal rudiments with concomitant changes in the signalling environment and gene expression profiles in both mouse and chick immobile embryos. Despite the clear relationship between movement and skeletogenesis, the precise mechanisms by which mechanical stimuli influence gene regulatory processes are not clear. The primary cilium enables cells to sense mechanical stimuli in the cellular environment, playing a crucial mechanosensory role during kidney development and in articular cartilage and bone but little is known about cilia on developing skeletal tissues. Here we examine the occurrence, length, position, and orientation of primary cilia across developing skeletal rudiments in mouse embryos during a period of pronounced mechanosensitivity and we report differences and similarities between wildtype and muscle-less mutant (Pax3Spd/Spd) rudiments. Strikingly, joint regions tend to have cilia positioned and oriented away from the joint, while there was a less obvious, but still significant, preferred position on the posterior aspect of cells within the proliferative and hypertrophic zones. Regions of the developing rudiments have characteristic proportions of ciliated cells, with more cilia in the resting and joint zones. Comparing wildtype to muscle-less mutant embryos, cilia are shorter in the mutant with no significant difference in the proportion of ciliated cells. Cilia at the mutant joint were also oriented away from the joint line.